2001
DOI: 10.1002/mds.1209
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of restless legs syndrome among men aged 18 to 64 years: An association with somatic disease and neuropsychiatric symptoms

Abstract: Standardized diagnostic criteria determined by the International Restless Legs Syndrome Study Group were used to investigate the current prevalence of restless legs syndrome (RLS). Possible associations between RLS and neuropsychiatric and somatic complaints were also investigated. A random sample of 4,000 men living in central Sweden were sent a questionnaire that included questions about sleep habits, symptoms of sleepiness, and somatic and neuropsychiatric complaints. Four symptom questions accepted as mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
234
6
14

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(270 citation statements)
references
References 17 publications
16
234
6
14
Order By: Relevance
“…More then 90% of patients with RLS have sleep disorders (3). On the other hand, epidemiologic data suggest higher prevalence of depression among patients with RLS (4)(5)(6)(7)(8). There is a strong relationship between insomnia and depression, as insomnia is a symptom of depression and also a risk factor to deteriorate depression (9).…”
Section: Introductionmentioning
confidence: 99%
“…More then 90% of patients with RLS have sleep disorders (3). On the other hand, epidemiologic data suggest higher prevalence of depression among patients with RLS (4)(5)(6)(7)(8). There is a strong relationship between insomnia and depression, as insomnia is a symptom of depression and also a risk factor to deteriorate depression (9).…”
Section: Introductionmentioning
confidence: 99%
“…RLS onset mostly occurs in the forties and fifties (4). It is clearly shown that the prevalence of RLS increases in relation to age, and it is more common amongst women (5,6). There is no laboratory test for the diagnosis of RLS, and it is based on standardized clinical diagnostic criteria by the International RLS Study Group (IRLSSG) (7).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, results from several crosssectional studies suggest an association of RLS with chronic kidney disease and cardiovascular diseases [4][5][6][7]. Secondary RLS in chronic kidney disease is frequently called "uremic RLS" [7].…”
Section: Introductionmentioning
confidence: 99%